Effects of total quality management applications and people management practices on the competitiveness of private sector companies. A case study in the Asir region, Saudi Arabia - Al-Shahrani, Badr Saeed Fayez (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims to examine the effects of Total Quality Management applications (TQM) and People Management Practices (PMP) on the competitiveness of private sector companies, and to know the links between these variables. Personnel management includes training and development, selection and recruitment, compensation, and employee performance evaluation, while TQM include continuous improvement, customer focus, senior management support, employee participation, and training, qualification, and education of employees. This survey included a composite sample of 624 organizations active in the private sector in the Asir region of the Kingdom of Saudi Arabia. The study adopted the Structural Equation Modeling (SEM) and the Partial Least Squares Path Modeling (PLS) method. Our results reveal major mechanisms: (1) TQM applications affect the PMP in different and unequal ways, but this effect This effect leads to an increase in the competitive advantages of the organizations. (2) Pecuniary compensation and rewarding employees have a positive and high impact on all TQM and cost management practices. (3) The practices of senior management related to evaluating the performance of employees help them in setting up rehabilitation, support, development, and education programs for their employees, and enables them to get to know them closely, and thus continue to adopt the applications of total quality management. (4) Good selection of workers and their employment helps to put pressure on costs, but for continuing their training, rehabilitation, and education, all of them achieve sustainable competitive advantages for the organization.